Biaxial strain improving carrier mobility for inorganic perovskite: ab initio Boltzmann transport equation. (8th February 2023) - Cao, Shuo; Su, Ye; Song, Ke-Ke; Qian, Ping; Yan, Yu; Shi, Li-Bin
Abstract: Inorganic halide perovskites have attracted interest due to their high efficiency and low cost. Considering the uncertainty of experimental measurements, it was important to predict the upper limit of carrier mobility. In this study, the ab initio Boltzmann transport equation, including all electron–phonon interactions, was used to accurately predict the mobilities of CsPbI3, CsSnI3, CsPbBr3, and CsSnBr3 . Using the iterative Boltzmann transport equation (IBTE), the calculated mobility for CsPbI3 is µ e = 512/ µ h = 379 cm 2  V −1  s −1, and Sn-based perovskite exhibited high hole mobility. The longitudinal optical phonons associated with the stretching between halogen anions and divalent metal cations were revealed to be the dominant scattering source for the carriers. Furthermore, the effect of biaxial strain on mobility was investigated. We observed that biaxial compressive strain could improve the mobility of CsPbI3 and CsPbBr3 . Surprisingly, under a compressive strain of − 2 %, the mobilities of CsPbI3 using IBTE approach were improved to µ e = 1176/ µ h = 936 cm 2  V −1  s −1 . It was revealed that the compressive strain could decrease the effective mass of CsPbI3 and CsPbBr3 .